Women's experiences and views of routine assessment for anxiety in pregnancy and after birth: A qualitative study - Yuill, C; Sinesi, A; Meades, R; Williams, LR; Delicate, A; Cheyne, H; Maxwell, M; Shakespeare, J; Alderdice, F; Leonard, R; Ayers, S; The MAP Study Team (Wiley, 2024)
Background Anxiety in pregnancy and postnatally is highly prevalent but under-recognized. To identify perinatal anxiety, assessment tools must be acceptable to women who are pregnant or postnatal.